PENGARUH PEREGANGAN TERHADAP PENURUNAN LAJU PERAMBATAN RETAK MATERIAL AL- 2024 T3 - Widyanto, Susilo Adi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2001)
Streching process of sheet materials is one of any process to increasing of material strength. But the effect of thisprocess on crack growth must investigate, the first for sheet materials are used as a plane structure.The test results show that the streching process of AL 2024 T3 materials of 3 % would produce of decreasingcrack growth rate, and 5 % of streching process would produce of increasing crack growth rate of materials.